Towards an APEX Syariah court in Malaysia - Shuaib, Farid Sufian; Mohd Kamal, Mohd Hisham; Ahmad Bustami, Tajul Aris; Othman, Noraini; Sulaiman, Mohamad Syafiq (2015)
Malaysia have 14 Syariah court systems. The main reason for this state of affairs is the distribution of legislative powers under the Federal Constitution between the federation and the States where Islam and Islamic Law are States matters. This paper looks at the consequences of having distinct Syariah court systems based on States the courts and the laws differ from one State to another. This paper looks at the legal possibility of having 1 apex court for all the 14 Syariah court systems to streamline the administration and decisions of Syariah courts. Proposals in having such a court are included in the discussion.